Real-time atomistic observation of structural phase transformations in individual hafnia nanorods - Bethany M. Hudak (Nature Portfolio, 2017)
The high-temperature tetragonal phase of HfO2 is technologically useful but difficult to stabilize at room temperature. Here, the authors observe in real-time the transformation of a HfO2nanorod from its room temperature to tetragonal phase, at 1000° less than its bulk temperature, suggesting that size confinement may kinetically trap this phase.